Silicon-germanium composite negative electrode material, preparation method thereof and lithium ion battery
Preparation of silicon-germanium composite negative electrode materials by molten salt electrolysis solves the problem of preparing high electrochemical properties materials in the prior art, achieving high specific capacity and excellent cycle stability, reducing production costs and improving safety.
Patent Information
- Application Number
- CN202411729404.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-04
AI Technical Summary
It is difficult to obtain silicon-germanium composite anode materials with high electrochemical properties through electrolysis in the prior art, and the traditional vapor deposition method is costly, risky and complex in process.
By using molten salt electrolysis method, the silicon germanium-based composite negative electrode material with diamond structure is prepared by heating and melting the electrolyte salt, mixing the silicon source with the germanium source and electrolyzing it.
The preparation of silicon-germanium composite anode material with high specific capacity, high rate performance and excellent cycle stability is achieved, reducing production costs, improving safety and process simplicity.
Smart Images

Figure CN119764367A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium-ion batteries, and in particular to a silicon-germanium composite negative electrode material, a preparation method thereof and a lithium-ion battery. Background Art
[0002] In recent years, due to the rapid development of industries such as electric vehicles, the demand for high energy density lithium-ion power batteries has become increasingly strong. The theoretical specific capacity of the currently commercially available graphite anode is 372 mAh / g, which is difficult to meet the demand for high energy density. Silicon and germanium materials in the IVA group are considered to be ideal candidates for the next generation of lithium-ion battery anode materials because of their high theoretical specific capacity and low lithium insertion potential. However, due to the electrochemical reaction between the two and Li + Alloying is accompanied by a dramatic volume expansion, causing serious pulverization, repeated formation of solid-electrolyte interface (SEI), and continuous consumption of active lithium, which ultimately leads to rapid failure of the negative electrode and short battery cycle life. The above shortcomings have seriously hindered the commercial application of silicon and germanium-based negative electrode materials.
[0003] As a semiconductor material, silicon has low electrical conductivity, which is not conducive to rapid electron conduction and difficult to meet the needs of high-rate charge and discharge. Due to its smaller band gap, germanium has an electrical conductivity of about 100 times that of silicon at room temperature and has high ionic conductivity. However, germanium resources are scarce and expensive, making it difficult to promote it alone as a negative electrode material on a large scale. Therefore, compared with silicon-based materials, silicon-germanium-based composite materials can greatly improve the conductivity of active materials and achieve higher comprehensive electrochemical performance at a relatively low cost.
[0004] Nano-sizing electrode materials is a common method to inhibit their volume expansion and pulverization. Vapor deposition is a common method for preparing silicon and germanium nanomaterials, and the reaction products have good purity and dispersibility. However, the vapor phase method has high production costs, cumbersome processes, and requires the use of dangerous gases such as silane. When using gases such as silane and dichlorosilane as silicon sources, they need to be heated to above 1000°C, which consumes a lot of energy.
[0005] Based on the above reasons, how to provide a simple, easy-to-implement and highly safe method for preparing a silicon-germanium composite negative electrode material to prepare a silicon-germanium-based composite negative electrode material with a high specific capacity is one of the important technical problems that need to be solved in this field. Summary of the invention
[0006] The main purpose of the present invention is to provide a silicon-germanium composite negative electrode material, a preparation method thereof and a lithium-ion battery, so as to solve the problem in the prior art that it is difficult to prepare a silicon-germanium composite negative electrode material with high electrochemical performance by electrolysis.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing a silicon-germanium composite negative electrode material, comprising: step S1, heating and melting an electrolyte salt to obtain a molten electrolyte salt; step S2, mixing a silicon source and a germanium source to obtain a precursor powder, and then pressing the precursor powder into a sheet to obtain a precursor sheet; step S3, using the molten electrolyte salt as an electrolyte and the precursor sheet as a working electrode, and performing electrolysis at a voltage of 1.0V~2.8V to obtain an electrolysis product at the working electrode, thereby obtaining a silicon-germanium composite negative electrode material.
[0008] Furthermore, the electrolysis includes a first electrolysis and a second electrolysis performed sequentially; the voltages of the first electrolysis and the second electrolysis are different and are each independently 1.1 V to 1.9 V; and the time of the first electrolysis and the second electrolysis is each independently 4 h to 8 h.
[0009] Furthermore, in step S1, the electrolyte salt is selected from one or more of KCl, NaCl, CaCl2, CaO, MgCl2, LiCl, KF, NaF, K2SiF6, Na2SiF6, Al2O3, MgF2, CaF2, LiF and BaF2.
[0010] Furthermore, the heating and melting temperature in step S1 is 500°C to 700°C.
[0011] Furthermore, in step S2, the molar ratio of the silicon source to the germanium source is (2.8-3.0):1.
[0012] Furthermore, in step S2, the silicon source is selected from one or more of silicon oxides, natural silicon-containing minerals and metal salts of silicon; and / or the germanium source is selected from one or more of germanium oxides, germanium hydroxides and metal salts of germanium.
[0013] Furthermore, in step S2, the precursor powder also includes a conductive material, and the content of the conductive material is 50% to 60% based on the total weight of the precursor powder as 100%; and / or the conductive material is selected from one or more of graphene, carbon nanotubes, graphite and MXene.
[0014] Furthermore, after obtaining the electrolysis product, step S3 also includes acid leaching, washing and drying the electrolysis product in sequence to obtain a silicon-germanium composite negative electrode material; the acid used for acid leaching is selected from one or more of hydrochloric acid, sulfuric acid and phosphoric acid; and / or the solvent used for washing is water and / or ethanol; and / or the drying is implemented by one or more of forced air drying, vacuum drying and freeze drying.
[0015] A second aspect of the present invention provides a silicon-germanium composite negative electrode material, which is prepared by the above-mentioned method for preparing the silicon-germanium composite negative electrode material.
[0016] The third aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet comprises the above-mentioned silicon-germanium composite negative electrode material.
[0017] By applying the technical solution of the present invention, a method for preparing a silicon-germanium-based composite negative electrode material with a diamond structure is provided by molten salt electrolysis. The process is simple and easy to synthesize. No hazardous gas is required or generated during the preparation process. At the same time, a composite negative electrode material with high specific capacity, high rate performance and excellent cycle stability can be prepared, which is expected to be widely used in secondary batteries such as high energy density lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0019] Figure 1 This is a SEM photograph of the silicon-germanium composite negative electrode material obtained in Example 1. DETAILED DESCRIPTION
[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0021] As described in the background technology, there is a problem in the prior art that it is difficult to prepare silicon-germanium composite negative electrode materials with high electrochemical performance by electrolysis. In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing silicon-germanium composite negative electrode materials, including: step S1, heating and melting the electrolyte salt to obtain a molten electrolyte salt; step S2, mixing the silicon source and the germanium source to obtain a precursor powder, and then pressing the precursor powder into a sheet to obtain a precursor sheet; step S3, using the molten electrolyte salt as an electrolyte and the precursor sheet as a working electrode, electrolyzing at a voltage of 1.0V~2.8V to obtain an electrolysis product at the working electrode, and then obtaining a silicon-germanium composite negative electrode material.
[0022] As mentioned in the background technology, the traditional vapor deposition method is costly, dangerous, and complex, and has great limitations. In contrast, the molten salt electrolysis method for preparing silicon-germanium-based composite negative electrode materials can greatly reduce costs, and change the composition, morphology and other characteristics of the composite negative electrode according to different uses. In addition, molten salt electrolysis does not require hazardous gases, which greatly improves production safety. The above-mentioned preparation method provided by the present invention can reduce the germanium element in the germanium source under electrochemical action through the molten salt electrolysis method. At the same time, the germanium element is combined with the silicon element in the silicon source in the molten electrolyte salt system to form a diamond-type crystal structure with stable chemical properties, optimize the transmission path of electrons and ions, and obtain a silicon-germanium negative electrode composite material with excellent electrochemical properties.
[0023] In particular, compared with other preparation methods in the prior art, such as vapor deposition, the preparation method based on electrolysis of molten salt provided by the present invention overcomes the template construction and separation difficulties faced by the CVD template method because molten salt electrolysis achieves morphology control through potential regulation, and ultimately achieves effective control of the morphology of germanium-based nanowires and nano-silicon.
[0024] In practical applications, after obtaining the precursor sheet, it is generally necessary to fix it on a molybdenum rod and use it together with the molybdenum rod as a working electrode. When the electrolysis is completed and the electrolysis product is obtained, the molybdenum mesh and molybdenum wire on it are removed. In addition, during the tableting process, a pressure of 0.1MPa~10MPa can be applied to make the precursor powder into a precursor sheet with a diameter of 6mm~20mm.
[0025] In addition, in step S3, a graphite rod electrode or an Ag / AgCl electrode can be used as a counter electrode. During the electrolysis process, in order to reduce the generation of impurities and improve the purity and electrochemical performance of the obtained negative electrode material, the electrolysis can be carried out under a protective atmosphere, and the protective gas can be one or more of an inert gas such as argon and nitrogen, preferably argon.
[0026] In order to control the morphology and composition of the obtained silicon-germanium negative electrode composite material at a finer level, thereby further optimizing its electrochemical performance, it is further preferred that the electrolysis includes a first electrolysis and a second electrolysis performed in sequence; the voltages of the first electrolysis and the second electrolysis are different, and are independently 1.1V to 1.9V; and the time of the first electrolysis and the second electrolysis are independently 4h to 8h. The voltage and time settings in the two-step electrolysis process can promote the silicon source and the germanium source to form a more ideal diamond-type crystal structure during the electrolysis process, thereby showing a more superior electrochemical performance.
[0027] Preferably, in step S1, the electrolyte salt is selected from one or more of KCl, NaCl, CaCl2, CaO, MgCl2, LiCl, KF, NaF, K2SiF6, Na2SiF6, Al2O3, MgF2, CaF2, LiF and BaF2, and in order to further optimize the structure of the obtained negative electrode material by utilizing synergistic effects, the electrolyte salt is preferably selected from at least two of CaCl2, NaCl, MgCl2, KCl, LiF, NaF and KF.
[0028] In several more typical embodiments, the electrolyte salt is CaCl2 and NaCl, and the molar ratio of CaCl2 and NaCl is (0.8~1.2):1; and / or, the electrolyte salt is CaCl2, NaCl and MgCl2, and the molar ratio of CaCl2, NaCl and MgCl2 is 2:2:(0.8~1.2); and / or, the electrolyte is KCl, NaCl and MgCl2, and the molar ratio of KCl, NaCl and MgCl2 is (1.8~2.2)3:5; and / or, the electrolyte is LiF, NaF and KF, and the molar ratio of LiF, NaF and KF is 2:(0.8~1.2):2. The inventors have conducted a combination of optimization of the molten electrolyte salt system through a large number of experiments to obtain the above-mentioned specific electrolyte salt system, which can further optimize the electrolysis process and prepare a silicon-germanium composite material with better performance.
[0029] Among them, especially when the electrolyte salt is CaCl2, NaCl and MgCl2, and the molar ratio of CaCl2, NaCl and MgCl2 is 2:2:(0.8~1.2), and when the electrolyte salt is KCl, NaCl and MgCl2, and the molar ratio of KCl, NaCl and MgCl2 is (1.8~2.2)3:5, the corresponding molten electrolyte salt system can be better compatible with the material structure formed by silicon germanium, thereby serving as a more preferred reaction condition, and more significantly improving the electrochemical properties of the obtained silicon germanium composite material.
[0030] Furthermore, the temperature of heating and melting in step S1 is 500° C. to 700° C. For the preparation method based on molten electrolyte salt provided by the present invention, when the conditions for heating the molten electrolyte salt are within this temperature range, the electrolyte salt can be fully melted, promoting the uniform reaction of the silicon source and the germanium source, and thus being more conducive to forming a silicon-germanium composite material with high capacity and good cycle stability.
[0031] In several typical embodiments, in order to promote the rational distribution of silicon and germanium elements in the composite material, form diamond-type crystals with more stable structure, and ultimately improve the electrochemical activity and stability of the material, the molar ratio of the silicon source to the germanium source in step S2 is preferably (2.8~3.0):1.
[0032] Furthermore, in step S2, the silicon source is selected from one or more of silicon oxides, natural silicon-containing minerals, and metal salts of silicon; and / or the germanium source is selected from one or more of germanium oxides, germanium hydroxides, and metal salts of germanium. The above silicon source and germanium source are widely available and easy to obtain, which can not only obtain composite negative electrode materials with excellent electrochemical performance, but also effectively reduce material costs, and improve the environmental protection and sustainability of the preparation method provided by the present invention.
[0033] In several typical embodiments, in order to improve the stability and controllability of the silicon source and the germanium source during the electrolysis process, thereby preparing a silicon-germanium composite material with more stable properties, the silicon oxide is preferably silicon dioxide and / or silicon monoxide; the natural silicon-containing mineral is montmorillonite and / or diatomaceous earth silicon; the metal salt of silicon is selected from one or more of CaSiO3, Na2SiO3 and MgSiO3; and / or, the germanium oxide is germanium dioxide and / or germanium monoxide; the germanium hydroxide is germanium dihydroxide and / or germanium tetrahydroxide; the metal salt of germanium is selected from one or more of Li4GeO4, Na2GeO3, Na2Ge2O5, Na2Ge4O9 and CaGeO3.
[0034] Further, in step S2, the precursor powder also includes a conductive material, and the content of the conductive material is 50% to 60% based on the total weight of the precursor powder as 100%. The introduction of the conductive material in this amount can further improve the conductivity of the resulting silicon-germanium composite negative electrode material, thereby improving the overall energy density and power density of the battery in which it is located. The conductive material is preferably selected from one or more of graphene, carbon nanotubes, graphite and MXene, and more preferably graphene and / or carbon nanotubes, so as to better adapt to the silicon-germanium composite system and obtain a composite negative electrode material with better electrochemical performance and more stable structure.
[0035] Furthermore, in order to remove excess electrolyte salt residues and purify the surface of the composite material obtained by electrolysis, thereby improving its purity and electrochemical activity, and ultimately making the obtained silicon-germanium composite negative electrode material exhibit more significant electrical performance advantages in lithium-ion batteries, it is preferred that after obtaining the electrolysis product, step S3 also includes acid leaching, washing and drying the electrolysis product in sequence to obtain the silicon-germanium composite negative electrode material.
[0036] Furthermore, the acid used for the acid leaching is selected from one or more of hydrochloric acid, sulfuric acid and phosphoric acid; and / or the solvent used for washing is water and / or ethanol; and / or the drying is implemented by one or more of forced air drying, vacuum drying and freeze drying. The selection of these more specific post-treatment methods can promote the stability and purity of the obtained electrolytic product during the post-treatment process, making the performance of the obtained silicon-germanium composite material more excellent. Preferably, the drying is implemented by vacuum drying, and the vacuum drying temperature is 70°C~80°C, and the time is 12h~14h, which can more effectively remove moisture and impurities in the obtained composite material and improve its purity and electrochemical activity.
[0037] And, in practical applications, the acid used for acid leaching is preferably 0.1 M HCl. And, preferably, washing includes: preparing a slurry with a solid content of 3% to 80% by mixing the electrolysis product after acid leaching with deionized water and / or anhydrous ethanol, dispersing it by ultrasonication for 0.5h to 48h, and then filtering it again with deionized water and / or anhydrous ethanol to complete washing. Preferably, the dispersion is ultrasonic dispersion and / or ball milling dispersion.
[0038] The second aspect of the present invention provides a silicon-germanium composite negative electrode material, which is prepared by the above-mentioned method for preparing the silicon-germanium composite negative electrode material. The silicon-germanium composite negative electrode material prepared by the preparation method provided by the present invention has a stable diamond-type crystal structure that is conducive to electron and ion transmission, thereby showing excellent electrochemical performance.
[0039] The third aspect of the present invention provides a lithium-ion battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the negative electrode sheet comprises the above-mentioned silicon-germanium composite negative electrode material. Since the above-mentioned silicon-germanium composite negative electrode material provided by the present invention has excellent electrochemical properties, when used as a negative electrode material in a lithium-ion battery, it can effectively improve the electrical performance of the battery during use, thereby making it exhibit an extremely high charge-discharge specific capacity.
[0040] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0041] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0042] Example 1
[0043] A method for preparing a silicon-germanium composite negative electrode material:
[0044] Step (1), weigh 750 g of CaCl2-NaCl (the molar ratio of CaCl2 to NaCl is 1:1) as electrolyte salt, mix well and put into a graphite crucible, place the graphite crucible containing the solid electrolyte salt into a stainless steel reaction container, and heat at 5 °C min -1 The temperature was raised to 300 °C at a heating rate of 1.5 °C and kept at this temperature for 48 hours to remove moisture from the solid electrolyte salt. The sealed reactor was then evacuated twice and an argon inert atmosphere was maintained. The temperature was then raised to 700 °C at the same rate to ensure that the solid electrolyte salt was completely melted to obtain a molten electrolyte salt.
[0045] Step (2): germanium dioxide is used as a germanium source and silicon dioxide is used as a silicon source. The silicon source and the germanium source are mixed in a molar ratio of 3:1 and sealed in a vial. The mixture is fully mixed in a three-dimensional mixer to obtain a precursor powder. 300 mg of the precursor powder is taken and pressed into a tablet at 6 MPa using a tablet press to obtain a precursor tablet with a diameter of 10 mm.
[0046] Step (3), wrap the precursor sheet with a molybdenum mesh, tie it to a molybdenum rod with molybdenum wire as a working electrode, and use a graphite rod as a counter electrode. In the molten electrolyte salt obtained in step (1), the voltage is increased to 1.9 V for a second electrolysis of 8 h after the first electrolysis at 1.3 V for 4 h. Collect the electrolysis product from the molybdenum mesh of the working electrode, soak it in dilute hydrochloric acid for one day, and perform ultrasonic dispersion. Then wash and filter with deionized water and ethanol to obtain a powder product. Finally, dry it at 60 ° C under vacuum for 12 h to obtain a silicon-germanium composite negative electrode material product.
[0047] The SEM images of the obtained materials are shown in Figure 1 , where the white part is the silicon-germanium composite negative electrode material sample.
[0048] Example 2
[0049] A method for preparing a silicon-germanium composite negative electrode material:
[0050] Step (1) is consistent with that in Example 1.
[0051] Step (2): germanium dioxide is used as a germanium source and diatomaceous earth is used as a silicon source. The silicon source and the germanium source are mixed in a molar ratio of 3:1 and sealed in a vial. The mixture is fully mixed in a three-dimensional mixer to obtain a precursor powder. 300 mg of the precursor powder is taken and pressed into a tablet at 6 MPa using a tablet press to obtain a precursor tablet with a diameter of 10 mm.
[0052] Step (3), wrap the precursor sheet with a molybdenum mesh, tie it to a molybdenum rod with molybdenum wire as a working electrode, and use a graphite rod as a counter electrode. Electrolyze at 1.3 V for 12 h in the molten electrolyte salt obtained in step (1). Collect the electrolysis product from the molybdenum mesh of the working electrode, soak it in dilute hydrochloric acid for one day, and perform ultrasonic dispersion. Then wash and filter with deionized water and ethanol to obtain a powder product. Finally, dry it at 60 ° C under vacuum conditions for 12 h to obtain a silicon-germanium composite negative electrode material product.
[0053] Example 3
[0054] A method for preparing a silicon-germanium composite negative electrode material:
[0055] Step (1) is consistent with that in Example 1.
[0056] Step (2): germanium monoxide is used as a germanium source and silicon monoxide is used as a silicon source. The silicon source and the germanium source are mixed in a molar ratio of 3:1 and sealed in a vial. The mixture is fully mixed in a three-dimensional mixer to obtain a precursor powder. 300 mg of the precursor powder is taken and pressed into a tablet at 6 MPa using a tablet press to obtain a precursor tablet with a diameter of 10 mm.
[0057] Step (3), wrap the precursor sheet with a molybdenum mesh, tie it to a molybdenum rod with molybdenum wire as a working electrode, and use a graphite rod as a counter electrode. In the molten electrolyte salt obtained in step (1), the voltage is reduced to 1.3V for a second electrolysis of 8 hours after the first electrolysis at 1.9V for 4 hours. Collect the electrolysis product from the molybdenum mesh of the working electrode, soak it in dilute hydrochloric acid for one day, and perform ultrasonic dispersion. Then wash and filter with deionized water and ethanol to obtain a powder product. Finally, dry it at 60 ° C under vacuum conditions for 12 hours to obtain a silicon-germanium composite negative electrode material product.
[0058] Example 4
[0059] A method for preparing a silicon-germanium composite negative electrode material:
[0060] Step (1), weigh 750 g of CaCl2-NaCl-MgCl2 (the molar ratio of CaCl2, NaCl and MgCl2 is 2:2:1) as electrolyte salt, mix them evenly and put them into a graphite crucible, place the graphite crucible containing the solid electrolyte salt in a stainless steel reaction container, and heat it at 5 °C min -1 The temperature was raised to 300 °C at a heating rate of 1.5 °C and kept at this temperature for 48 hours to remove moisture from the solid electrolyte salt. The sealed reactor was then evacuated twice and an argon inert atmosphere was maintained. The temperature was then raised to 600 °C at the same rate to ensure that the solid electrolyte salt was completely melted to obtain a molten electrolyte salt.
[0061] Step (2): germanium dioxide is used as a germanium source, silicon dioxide is used as a silicon source, and the silicon source, germanium source and graphene are mixed to obtain a mixed powder. The molar ratio of the silicon source to the germanium source in the precursor is 3:1, and the graphene accounts for 50% of the total mass of the precursor. The obtained mixed powder is then sealed in a vial and fully mixed in a three-dimensional mixer to obtain a precursor powder. 300 mg of the precursor powder is taken and tableted using a tablet press at 6 MPa to obtain a precursor tablet with a diameter of 10 mm.
[0062] Step (3) is consistent with that in Example 1.
[0063] Example 5
[0064] A method for preparing a silicon-germanium composite negative electrode material:
[0065] Step (1), weigh 750 g of KCl-NaCl-MgCl2 (the molar ratio of KCl, NaCl and MgCl2 is 2:3:5) as electrolyte salt, mix them evenly and put them into a graphite crucible, place the graphite crucible containing the solid electrolyte salt into a stainless steel reaction container, and heat it at 5°C min -1 The temperature was raised to 300 °C at a heating rate of 1.5 °C and kept at this temperature for 48 hours to remove the moisture in the solid electrolyte salt. The sealed reactor was then evacuated twice and an argon inert atmosphere was maintained. The temperature was then raised to 650 °C at the same rate to ensure that the solid electrolyte salt was completely melted to obtain a molten electrolyte salt.
[0066] Step (2): germanium monoxide is used as a germanium source, diatomaceous earth is used as a silicon source, and the silicon source, germanium source and carbon nanotubes are mixed to obtain a mixed powder. The molar ratio of the silicon source to the germanium source in the precursor is 3:1, and the carbon nanotubes account for 50% of the total mass of the precursor. The obtained mixed powder is then sealed in a vial and fully mixed in a three-dimensional mixer to obtain a precursor powder. 300 mg of the precursor powder is taken and tableted using a tablet press at 6 MPa to obtain a precursor tablet with a diameter of 10 mm.
[0067] Step (3) is consistent with that in Example 1.
[0068] Example 6
[0069] A method for preparing a silicon-germanium composite negative electrode material:
[0070] Step (1), weigh 750 g of LiF-NaF-KF (the molar ratio of LiF, NaF and KF is 2:1:2) as electrolyte salt, mix them evenly and put them into a graphite crucible, place the graphite crucible containing the solid electrolyte salt in a stainless steel reaction container, and heat it at 5 °C min -1The temperature was raised to 300 °C at a heating rate of 1.5 °C and kept at this temperature for 48 hours to remove moisture from the solid electrolyte salt. The sealed reactor was then evacuated twice and an argon inert atmosphere was maintained. The temperature was then raised to 500 °C at the same rate to ensure that the solid electrolyte salt was completely melted to obtain a molten electrolyte salt.
[0071] Step (2): germanium dioxide is used as a germanium source, sodium silicate is used as a silicon source, and the silicon source and the germanium source are mixed at a molar ratio of 3:1 to obtain a mixed powder. The obtained mixed powder is then sealed in a vial and fully mixed in a three-dimensional mixer to obtain a precursor powder. 300 mg of the precursor powder is taken and tableted using a tablet press at 6 MPa to obtain a precursor tablet with a diameter of 10 mm.
[0072] Step (3) is consistent with that in Example 1.
[0073] Example 7
[0074] A method for preparing a silicon-germanium composite negative electrode material:
[0075] The only difference between this embodiment and embodiment 1 is that the temperature for heating and melting the molten electrolyte salt in step (1) is changed from 700° C. to 800° C.
[0076] Example 8
[0077] A method for preparing a silicon-germanium composite negative electrode material:
[0078] The only difference between this embodiment and embodiment 1 is that the temperature for heating and melting the molten electrolyte salt in step (1) is changed from 700° C. to 400° C.
[0079] Example 9
[0080] A method for preparing a silicon-germanium composite negative electrode material:
[0081] The only difference between this embodiment and embodiment 1 is that the molar ratio of the silicon source to the germanium source in step (2) is changed from 3:1 to 2:1.
[0082] Example 10
[0083] A method for preparing a silicon-germanium composite negative electrode material:
[0084] The only difference between this embodiment and embodiment 1 is that the molar ratio of the silicon source to the germanium source in step (2) is changed from 3:1 to 4:1.
[0085] Embodiment 11
[0086] A method for preparing a silicon-germanium composite negative electrode material:
[0087] The only difference between this embodiment and embodiment 4 is that the proportion of graphene in the total mass of the precursor in step (2) is changed from 50% to 40%.
[0088] Example 12
[0089] A method for preparing a silicon-germanium composite negative electrode material:
[0090] The only difference between this embodiment and embodiment 4 is that the proportion of graphene in the total mass of the precursor in step (2) is changed from 50% to 80%.
[0091] Embodiment 13
[0092] A method for preparing a silicon-germanium composite negative electrode material:
[0093] The only difference between this embodiment and embodiment 1 is that in step (3), after obtaining the electrolysis product, no acid leaching is performed, but subsequent ultrasonic dispersion, washing and drying are directly performed.
[0094] Comparative Example 1
[0095] A method for preparing a silicon-germanium composite negative electrode material:
[0096] The difference between this comparative example and Example 1 is that step (1) is not performed, but CaCl2 and NaCl are mixed in a molar ratio of 1:1 and added to deionized water to prepare a 1M salt solution to replace the molten electrolyte salt.
[0097] Comparative Example 2
[0098] A method for preparing a silicon-germanium composite negative electrode material:
[0099] The only difference between this comparative example and Example 2 is that the voltage of electrolysis in step (3) is changed from 1.3 V to 0.5 V.
[0100] Comparative Example 3
[0101] A method for preparing a silicon-germanium composite negative electrode material:
[0102] The only difference between this comparative example and Example 2 is that the voltage of electrolysis in step (3) is changed from 1.3 V to 3.2 V.
[0103] Preparation and performance testing of battery samples:
[0104] Using deionized water as solvent, the negative electrode materials obtained in each embodiment and comparative example were mixed with Super P and carboxymethyl cellulose (CMC) in a mass ratio of 80:10:10 to obtain a slurry, and then the slurry was coated on a copper foil by a coating machine, and dried in a vacuum oven at 80°C for 12 h to prepare an electrode disc with a diameter of 10 mm.
[0105] Afterwards, in an argon glove box (water content less than 0.1 ppm; oxygen and water content less than 0.1 ppm), the obtained electrode sheet was used as the working electrode, the metal lithium sheet was used as the counter electrode, LiPF6 solute was dissolved in tetrahydrofuran and 2-methyltetrahydrofuran solvent (volume ratio of 1:1) at a concentration of 2 mol / L as the electrolyte, and polypropylene microporous membrane Celgard 2100 was used as the separator to assemble into a CR 2032 type button half-cell sample.
[0106] The assembled battery samples were charged and discharged using a blue battery tester with a voltage range of 0.01V~1.5V and a charge / discharge rate of 100 mA·g -1 The battery samples were charged and discharged at a current density of , and the first cycle charging specific capacity of the battery samples corresponding to the embodiments and comparative examples were obtained, as shown in Table 1 below.
[0107] Table 1
[0108]
[0109] From the above description, it can be seen that the above embodiment of the present invention realizes the preparation of silicon-germanium composite material by electrolysis. When the obtained silicon-germanium composite material is used as a negative electrode material in a lithium-ion battery, the corresponding lithium-ion battery exhibits excellent charge specific capacity.
[0110] Specifically, by optimizing the process parameters of molten salt electrolysis, the morphology and size of germanium and silicon can be controlled. Germanium exists in the form of nanowires to achieve an excellent ion-conducting network for battery composite negative electrode materials, and silicon particles exist at the nanoscale to increase the reaction area of the electrochemical reaction, thereby effectively improving the charging capacity.
[0111] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a silicon-germanium composite negative electrode material, characterized in that: include: Step S1, heating and melting the electrolyte salt to obtain a molten electrolyte salt; Step S2, mixing a silicon source and a germanium source to obtain a precursor powder, and then pressing the precursor powder into tablets to obtain a precursor tablet; Step S3, using the molten electrolyte salt as an electrolyte and the precursor sheet as a working electrode, electrolysis is performed at a voltage of 1.0V to 2.8V to obtain an electrolysis product at the working electrode, thereby obtaining the silicon-germanium composite negative electrode material.
2. The method for preparing the silicon-germanium composite negative electrode material according to claim 1, characterized in that: The electrolysis comprises a first electrolysis and a second electrolysis performed sequentially; The voltage of the first electrolysis is different from that of the second electrolysis, and each is independently 1.1 V to 1.9 V; The time of the first electrolysis and the second electrolysis are each independently 4h~8h.
3. The method for preparing the silicon-germanium composite negative electrode material according to claim 2, characterized in that: In step S1, the electrolyte salt is selected from one or more of KCl, NaCl, CaCl2, CaO, MgCl2, LiCl, KF, NaF, K2SiF6, Na2SiF6, Al2O3, MgF2, CaF2, LiF and BaF2.
4. The method for preparing the silicon-germanium composite negative electrode material according to claim 3, characterized in that: The heating and melting temperature in step S1 is 500°C to 700°C.
5. The method for preparing a silicon-germanium composite negative electrode material according to any one of claims 1 to 4, characterized in that: In step S2, the molar ratio of the silicon source to the germanium source is (2.8-3.0):
1.
6. The method for preparing the silicon-germanium composite negative electrode material according to claim 5, characterized in that: In step S2, The silicon source is selected from one or more of silicon oxides, natural silicon-containing minerals and metal salts of silicon; and / or, The germanium source is selected from one or more of germanium oxides, germanium hydroxides and metal salts of germanium.
7. The method for preparing a silicon-germanium composite negative electrode material according to any one of claims 1 to 4, characterized in that: In step S2, The precursor powder further includes a conductive material, and based on the total weight of the precursor powder being 100%, the content of the conductive material is 50% to 60%; and / or, The conductive material is selected from one or more of graphene, carbon nanotubes, graphite and MXene.
8. The method for preparing a silicon-germanium composite negative electrode material according to any one of claims 1 to 4, characterized in that: After obtaining the electrolysis product, step S3 further includes: acid leaching, washing and drying the electrolysis product in sequence to obtain the silicon-germanium composite negative electrode material; The acid used for the acid leaching is selected from one or more of hydrochloric acid, sulfuric acid and phosphoric acid; and / or the solvent used for the washing is water and / or ethanol; and / or the drying is implemented by one or more of forced air drying, vacuum drying and freeze drying.
9. A silicon-germanium composite negative electrode material, characterized in that: The silicon-germanium composite negative electrode material is prepared by the method for preparing the silicon-germanium composite negative electrode material according to any one of claims 1 to 8.
10. A lithium ion battery, comprising a positive electrode sheet and a negative electrode sheet, characterized in that: The negative electrode plate includes the silicon-germanium composite negative electrode material according to claim 9.